2020
DOI: 10.3389/fpsyg.2019.02962
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Mindsets, and Success in Navy SEALs Special Warfare Training

Abstract: Mindsets can impact an individual's performance in stressful experiences such as public speaking or receiving negative feedback. Yet we know little about the boundary conditions of where these mindsets predict success, and where they may become irrelevant or even maladaptive. The current research asks whether mindsets are beneficial in environments of extreme physical and mental stress using participants undergoing the notoriously challenging Navy SEALs training. We hypothesized that participants with stress-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 54 publications
2
26
1
1
Order By: Relevance
“…Interestingly, a recent study showed that stress mind-set predicted success in a 7-week NAVY SEALS training, known to be physically and mentally very challenging [44]. "Stress is enhancing" mindset was inversely related to dropout and positively to obstacle course time [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study showed that stress mind-set predicted success in a 7-week NAVY SEALS training, known to be physically and mentally very challenging [44]. "Stress is enhancing" mindset was inversely related to dropout and positively to obstacle course time [44].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that stress mind-set predicted success in a 7-week NAVY SEALS training, known to be physically and mentally very challenging [44]. "Stress is enhancing" mindset was inversely related to dropout and positively to obstacle course time [44]. It is worth noting, that all the previous studies investigating psychological metrics and drop-out have used longer exposure time frame (from 25 days up to several months) compared to shorter one used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Limited theorists show less goal-persistence, have higher BMIs, and lower subjective well-being (for review, see Francis & Job, 2018). But early evidence suggests that limited willpower beliefs might have some positive interpersonal consequences-for instance, in a sample of Navy SEALs, nonlimited willpower theorists were rated more negatively by their peers and instructors than their limited theorist counterparts, potentially due to nonlimited theorists having higher standards and less empathy for their peers (Smith et al, 2018). If limited theorists are more likely to anticipate and empathize with other people's fatigue, then they might have an advantage when supporting their romantic partners-if, that is, they can overcome their own feelings of depletion.…”
Section: Why Limited Willpower Theorists Might Provide More Supportmentioning
confidence: 99%
“…If this is true, holding a more limited willpower theory may be associated with less intention to provide support. (2) However, limited theorists are more likely to anticipate and relate to other people’s experiences of depletion (Francis & Inzlicht, 2017; Smith, Young, & Crum, 2018)–if limited theorists are more likely to see their partner as fatigued or unhappy, they may be more motivated and willing to provide support for their partner. If this is true, a more limited willpower theory may be associated with more intention to provide support.…”
mentioning
confidence: 99%
“…Initial evidence does suggest that holding a limited willpower theory might be associated with some positive interpersonal outcomes; one recent study found that limited willpower theorists were viewed more positively by peers and instructors (Smith et al ., 2020) and a second study found that limited willpower theorists were more likely to perceive their romantic partner as fatigued in the evenings, which indirectly predicted more intended provision of support (Francis et al ., 2020). It is possible that those who believe that willpower is limited may be better able to empathize and respond with understanding to those around them, particularly when those around them have experienced high levels of demand.…”
Section: Introductionmentioning
confidence: 99%